The factors affecting the employment of Halal industry with in Narathiwat Province - Sakulrat, Benjaree; Sojipan, Weerasak; Palasai, Wasan (Princess of Naradhiwas University Journal, 2019)
This research aims to study the labour situation in halal production sector and the factors that affect the employment of the procurement of Narathiwat Province. The research results in the amount of the halal industrial labour data that has been properly registered within Narathiwat province. There are a total of 24 industrial factories. There are 256 male workers There are a total of 227 female workers from the Narathiwat provincial industry office of 24 factories using a query as a data storage tool. Focus on production to meet the needs of people in Narathiwat province and related agencies. Most of them are small, medium and small enterprises. Family investments are primarily used. Factors affecting the employment of labor are the circumstances and potential of labor to accommodate the economic area within the province. As a potential and administrative organization of the establishment. It has been promoting a fully integrated halal industry entrepreneur. The form of mechanical and process development of workers to enhance the competitiveness of the province. Promoting the role of a government agency to develop the halal industry and understanding the people in the area to organize the central halal in the province. Policy to promote halal industry in production resources and human resources The standard of halal products is acceptable. Policy on promoting the support of provinces in the international investment The competitiveness of entrepreneurs and severity problems in three southern border provinces Building confidence in Thailand’s halal industry